MENINGKATKAN BUDAYA LITERASI MELALUI PENDEKATAN SAINTIFIK (PROBLEM BASED LEARNING) BERFALSAFAH TRI HITA KARANA MENUJU SISWA BERKARAKTER - I Gusti Agung Made Gede Mudana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
The school literacy movement was developed based on nine priority agendas (Nawacita)aimed at growing and developing reading and writing skills. A person is said to be literate if heis able to understand something because reading the right information and doing somethingbased on his understanding of the contents of the reading. Sensitivity or literacy in a personcertainly does not just appear. No human is literate from birth. Creating literate generationrequires a long process and conducive means. This process starts from a small and familyenvironment, then is supported or developed in schools, social settings, and work environments.Literacy culture is also strongly associated with learning patterns in schools and the availabilityof reading material in libraries. In this case, the scientific approach to the philosophy of TriHita Karana is able to direct students to think inductively so that it is expected to be able todevelop creativity and improve literacy culture in schools. By instilling the concept of Tri HitaKarana in scientific learning, it can be expected that students will be able to think critically andhave a strong character in establishing good communication with its creator, nature, and others.